Copyright Dispute Resolution in Indonesia - Alum Simbolon; Japansen Sinaga (Sociological Jurisprudence Journal, 2025)
Settlement of Copyright disputes can be done through Alternative dispute resolution, arbitration, in the Commercial Court. Copyright violations often occur so that legal settlement is needed so that the Community as creators can obtain legal certainty. Settlement of copyright disputes in the Commercial Court, this court's competence is absolute competence (absolute competentie) because it is stated that other courts besides the commercial court are not authorized to handle the settlement of copyright disputes and other intellectual property rights, except for Trade Secrets and Plant Varieties. Settlement of copyright disputes through non-litigation is often referred to as copyright settlement carried out outside the court. The existence of dispute resolutions outside the court is a breakthrough because many cases are piling up in the court that have not been resolved.